História da educação matemática no Brasil: contribuições das pesquisas para professores da educação básica - Gonçalves, Francisco Djnnathan da Silva (2015)
This dissertation of Master Science degree is part final result from many research which has as purpose of study thedissertations and theses defended in Brazil, in graduate programs in the areas of education, mathematics education, teach of natural sciences and mathematics and related areas, between 1990 to 2010, which were main area of research the history of mathematics and the history of education. According to our purpose, we take as the study part research related to the history of mathematics education, present in the two areas mentioned earlier. In this direction, in general objective was to analyze how to production in this area, during the period described, can contribute to the educational actions of teachers who teach mathematics in basic education. In this way, check the types of methodological approaches included, in a didactic wrong for teaching mathematics at the basic level and the list of possible mathematical content present on these dissertations and theses analyzed. So, from the study conducted by Mendes in the year 2014, on the productions in the area defended history of mathematics education, available at the Bank of data in Brazil the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), as well as in the digital libraries of the graduate programs in the country in the strict sense, we organize the criteria for identification and classification of the material. We emphasize the important contribution in Brazil of the annals of the first 10 National Meetings of Education Mathematics (ENEM) it correlated and structured information about the consolidation of the research field of mathematics education, specifically, the area which the contents of this dissertation appropriated. With this, the results showed the existence of a group of dissertations and theses that have didactic and conceptual potential for use in initial and continuing training of teachers of mathematical discipline. It was evident that such contributions are not explicit, since it is not mentioned that this was the intention of the research investigated. It is however, those interested a little more study and adaptation of the material produced, so you can use this information in the classroom.